Implementasi Aplikasi Parsiajaran Berbasis Gamifikasi Dan Budaya Batak Angkola Untuk Meningkatkan Literasi Dan Numerasi Siswa SDN 200112 Padangsidimpuan - Nasution, Eni Sumanti; Kasmawati; Nasution, Fauziah; Harahap, Tinur Rahmawati; Tambunan, Elissa Evawani; Rafii, Ahmad (Yayasan Kajian Riset dan Pengembangan RADISI, 2025)
This community service program aims to address the low literacy and numeracy levels of students at SDN 200112 Padangsidimpuan through the implementation of the Parsiajaran Application based on gamification and Batak Angkola culture. The main problems faced are National Assessment (ANBK) scores for literacy (428) and numeracy (416) which are below the national average, dominance of lecture methods without local cultural integration, and limited use of technology in learning. The implementation method uses a service learning approach through stages of planning, socialization, training, technology implementation, mentoring, and evaluation. The program involved 96 participants consisting of 24 teachers and 72 sixth-grade students. Implementation results showed significant improvements with literacy scores increasing 12.4% (from 428 to 481) and numeracy 15.8% (from 416 to 482). As many as 85% of students actively use the application, 90% of teachers are trained to implement technology and culture-based learning, and 65% of teacher lesson plans integrate Batak Angkola cultural elements. This program successfully created more interactive learning, strengthened students' cultural identity, and increased learning motivation through a gamification approach that is contextual with local culture.